Wireless Internet 7th International ICST Conference, WICON 2013, Shanghai, China, April 11-12, 2013, Revised Selected Papers - Qian, Hua.; Kang, Kai. (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering, 2013)
This book constitutes the thoroughly refereed post-conference proceedings of the 7th International ICST Conference on Wireless Internet, WICON 2013, held in Shanghai, China, in April 2012. The 20 revised full papers were carefully reviewed and selected from numerous submissions. The papers cover topics such as vehicular communications and heterogeneous networks, cognitive radio and multi-antenna systems, networks and beyond, ad hoc and mesh networks.